A Critical Perspective on Short-term Mobility: The Kazakhstan Experience - Kuzhabekova, Aliya; Ispambetova, Botagoz (International Higher Education, 2023)
Based on the results of interviews with Kazakhstani government-sponsored international students, this article argues that the benefits of short-term mobility do not accrue equally to the host and sending institutions. Northern institutions are the main beneficiaries, generating revenue from international student fees. Southern institutions are often degraded to secondary roles in capacity-building projects, whereby they must perform more effort-intensive and seldom recognized administrative and field responsibilities, while gaining few results.